2017
DOI: 10.3748/wjg.v23.i42.7572
|View full text |Cite
|
Sign up to set email alerts
|

Novel D-galactosamine-induced cynomolgus monkey model of acute liver failure

Abstract: AIMTo establish a simplified, reproducible D-galactosamine-induced cynomolgus monkey model of acute liver failure having an appropriate treatment window.METHODSSixteen cynomolgus monkeys were randomly divided into four groups (A, B, C and D) after intracranial pressure (ICP) sensor implantation. D-galactosamine at 0.3, 0.25, 0.20 + 0.05 (24 h interval), and 0.20 g/kg body weight, respectively, was injected via the small saphenous vein. Vital signs, ICP, biochemical indices, and inflammatory factors were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Numerous cytokines such as interleukin family, colony-stimulating factor and chemokines formed a complex, overlapping communication network. Based on our data, significant increase of inflammatory markers as IL-1β, IL-6, and TNF-α was detected, which was consistent with previous studies and showed to be positively correlated with liver cell necrosis (Pan et al, 2016; Feng et al, 2017). Higher levels of colony stimulating factors including GM-CSF, M-CSF, and G-CSF were found in rats with D-GalN injection.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous cytokines such as interleukin family, colony-stimulating factor and chemokines formed a complex, overlapping communication network. Based on our data, significant increase of inflammatory markers as IL-1β, IL-6, and TNF-α was detected, which was consistent with previous studies and showed to be positively correlated with liver cell necrosis (Pan et al, 2016; Feng et al, 2017). Higher levels of colony stimulating factors including GM-CSF, M-CSF, and G-CSF were found in rats with D-GalN injection.…”
Section: Discussionsupporting
confidence: 92%
“…At present, there are two main methods to construct ALF animal models: drug model [7,22,23] and surgical model [6,24,25]. Compared with the drug model, surgical ALF animal model requires high surgical techniques, and surgical trauma affects the pathophysiology of liver, which is different from the physiological and biochemical manifestations of clinical ALF.…”
Section: Discussionmentioning
confidence: 99%
“…The most common used drugs for inducing ALF mainly include D-galactosamine (D-gal) [7,22], acetaminophen (APAP) [26][27][28][29], thioacetamide (TAA) [30], and carbon tetrachloride (CCl 4 ) [31]. In most drug models of ALF, there are nephrotoxicity, cardiotoxicity and other organ damage besides hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…D-GalN is the most commonly used hepatotoxic agent in large animal models of ALF, in which D-GalN is administered directly through the jugular or central vein. 0.5–1.5 g kg −1 D-GalN can induce fulminant hepatic failure in pigs [ 8 , 53 , 54 ], while 0.2–0.3 g kg −1 D-GalN is used for constructing D-GalN-related cynomolgus monkey model of ALF [ 55 , 56 ]. LPS triggers the activation of Kupffer cells and production of tumor necrosis factor-α (TNF-α), resulting in inflammatory necrosis of hepatocytes.…”
Section: Mechanism Of Nanomedicines For Acute Liver Failure Therapymentioning
confidence: 99%